An Integrated Framework for an Educational Early Warning System with Mentor Matching - D. V. D. S. Abeysinghe; M. S. D. Fernando (IAFOR Journal of Education)
"Education is the key to success,” one of the most heard motivational statements by all of us. People engage in education at different phases of our lives in various forms. Among them, university education plays a vital role in our academic and professional lives. During university education many undergraduates will face several challenges demanding from educational matters to socio-economic problems. In such situations, many undergraduates tend to abandon the degree programs halfway leaving them incomplete. Hence creating an Educational Early Warning Systems (EEWS) to predict and identify at-risk students in the early stages of the degree programs will improve the graduating ratio against the dropouts. Further, mentoring is another aspect in education where it can be used in undergraduate studies to address students individually. There exist many separate frameworks for EEWS and mentoring, but there exists a lacuna for an integrated framework for the two aspects. Having an integrated framework to identify at-risk undergraduates and matching the best matched mentor would be more impactful and effective for the universities to control dropouts. This study has proposed an integrated framework namely as “GRADGROOM” as a solution to the identified lacuna by extending EEWS framework with mentor matching which performs at-risk undergraduate prediction and mentor-mentee matching for them. Through two case studies at a local university, the study has concluded that a proper mentoring process conducted immediately after being identified as at-risk students will be highly beneficial to reshape their study patterns to align with the correct route of studying.